Audit Tata Kelola Teknologi Informasi Untuk Mengontrol Manajemen Kualitas Menggunakan Cobit 4.1 (Studi Kasus : PT Nikkatsu Electric Works) - Rauf Fauzan; Rani Latifah (Maranatha University Press, 2015)
Abstract — Information technology has become an important part in the organization, particularly for profit-oriented business organizations. PT Nikkatsu Electric Work is one of the companies that require information technology governance. Information technology governance need to be evaluated to establish the condition of the company in terms of IT performance management to control the quality.One of the important things that can help to evaluate the underlying performance of information technology is a framework for information technology governance that provides the basis for development of information technology governance based on COBIT. Analysis and evaluation are conducted by the COBIT 4.1 framework on ME1 domain. It is monitoring and evaluating the performance of information technology. Method or tool used is AHP calculation.Results of the analysis is that the evaluation of the level of maturity and performance of IT are at level 2. While the level of expectations of the company are at level 4. Recommended strategy of 6 aspects of the attributes of maturity is required to achieve the expected level. Keywords— IT Governance, Level Maturity, COBIT 4.1